Math Problem Statement
Use the laws to show that -(p^q) v (p^q) = -p
Solution
We are tasked with showing that the expression simplifies to . To do this, we'll use some standard logical laws, including De Morgan's Law, Distributive Law, and Absorption Law. Let's break it down step by step.
Expression:
Step 1: Apply De Morgan's Law
De Morgan's law tells us that: So, applying this law to the negation of , we get:
Step 2: Distribute over
Now, apply the Distributive Law: We will handle both parts separately.
Step 3: Simplify using Absorption Law
Let’s simplify first. By Absorption Law, we know: This is because if is true, the entire disjunction is true regardless of ; and if is false, would be false too.
Now let’s simplify . By another application of Absorption Law: This is because if is true, the whole disjunction is true regardless of , and if is false, then the truth of determines the value of the disjunction.
Step 4: Simplified expression
After simplification, the expression becomes:
Step 5: Apply the Law of Excluded Middle
The Law of Excluded Middle tells us that: This is always true since either or will hold in every situation.
Step 6: Simplification
However, this is not yet fully aligned with . We must have misinterpreted some intermediate simplifications.
Can you clarify what
Ask a new question for Free
By Image
Drop file here or Click Here to upload
Math Problem Analysis
Mathematical Concepts
Propositional Logic
Boolean Algebra
Logical Laws
Formulas
De Morgan's Law: ¬(p ∧ q) = ¬p ∨ ¬q
Distributive Law: A ∧ (B ∨ C) = (A ∧ B) ∨ (A ∧ C)
Absorption Law: p ∨ (p ∧ q) = p
Law of Excluded Middle: p ∨ ¬p = True
Theorems
De Morgan's Theorem
Distributive Theorem
Absorption Theorem
Law of Excluded Middle
Suitable Grade Level
Undergraduate or Advanced High School
Related Recommendation
Proving Logical Equivalence: (p ∧ ¬q) ∨ (p ∧ q) = p Using Distributive, Tautology, and Identity Laws
Proving Logical Equivalence: ¬(p ∨ (¬p ∧ q)) ≡ ¬p ∧ ¬q
Prove Logical Equivalence ¬(p ∨ (¬p ∧ q)) ≡ (¬p ∧ ¬q) using Identities
Prove Logical Equivalence Using Double Negation and Boolean Laws
Proof of Logical Equivalence in Boolean Algebra